Pengaruh Inokulasi Pseudomonas spp. Indigenus terhadap Penyakit Akar Gada dan Pertumbuhan Tanaman Kubis (Brassica oleracea L.) - IDA AYU GEDE DIANGGI ADIATHY; NI WAYAN SUNITI; I KETUT SUADA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2017)
The Effect of Pseudomonas spp. Indigenous Inoculation against Clubroot Disease and Cabbage (Brassica oleracea L.) Plant Growth Clubroot that caused by Plasmodiophora brassicae Wor. is a disease that can cause great losses to cabbage. Utilization of biological agents such as indigenous Pseudomonas spp. become an alternative option to be recommended to suppress the disease, because it is environmentally friendly and safe for the balance within ecosystem. The aim of this study was to obtain the most effective isolate of indigenous Pseudomonas spp. in suppressing clubroot disease and promoting growth of cabbage plants. The results showed there were three best effective isolates which able to suppress the clubroot disease as well increase the plant growth. The isolates were isolated from Brassica oleracea var. italica (Pf5), isolated from Brassica oleracea capitata var. rubra (Pf8), and isolated from Eruca sativa (Pf12).